1988
DOI: 10.1002/smj.4250090408
|View full text |Cite
|
Sign up to set email alerts
|

Responses to externally induced innovation: Their effects on organizational performance

Abstract: Innovation may be externally induced; that is, an external threat or challenge such as the accident at the Three Mile Island (TMl) nuclear power plant sets the stage for outside parties such as the Nuclear Regulatory Commission (NRC) to propose that new practices be adopted. Managers then must make choices about how their organizations will respond. This study shows how prior performance can affect organizational responses and how these responses in turn can affect subsequent performance. Vicious cycles are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Atuahene-Gima 1996; Han et al 1998;Li and Atuahene-Gima 2001), process innovation (e.g. Marcus 1988;Ittner and Larcker 1997;Whittington et al 1999;Knott 2001;Baer and Frese 2003) and organizational innovation (e.g. Damanpour 1991;Sapprasert and Clausen 2012).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Atuahene-Gima 1996; Han et al 1998;Li and Atuahene-Gima 2001), process innovation (e.g. Marcus 1988;Ittner and Larcker 1997;Whittington et al 1999;Knott 2001;Baer and Frese 2003) and organizational innovation (e.g. Damanpour 1991;Sapprasert and Clausen 2012).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Others have hypothesized that the preferable alternative is to convert the threat (environmental liability) into an opportunity (Marcus, 1988). Advocates of Total Quality Environmental Management (Sharfman and Dean, 1991;Shrivastava, 1995:944) argue that focusing on the environment 'will optimize the ecological performance of the entire corporate system'.…”
Section: Beneficial Environmental Controlsmentioning
confidence: 99%
“…Rather, they focus either on the politics of regulation and regulatory reform after Three Mile Island (Temples, 1982), the enforcement practices of NRC inspectors (Nelkin, 1981), or on industry-wide data in attempts to establish the factors associated with noncompliance (Feinstein, 1989) and innovation (Marcus, 1988). These studies tend to evince vestiges of older paradigms -and perhaps an older way of doing business in the California Public Utility Commission (CPUC), the Office of Emergency Services (OES), Occupational Health and Safety Agency (CAL/OSHA), and the state Nuclear Safety Review Group (NSRG).…”
Section: Demand and Responsementioning
confidence: 99%
“…Marcus (1988) found that some plants anticipate and even implement new safety concepts before they are required to do so.…”
Section: Demand and Responsementioning
confidence: 99%